Assessment of Efficacy of Faecal Antigen Detection Kit and Occurrence of Sepsis in Canine Parvovirus Enteritis in Dogs - Chauhan, Divya; Srivastava, Ashish; Singh, Ajay Pratap; Srivastava, Mukesh Kumar; Verma, Med Ram (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Canine parvovirus (CPV) enteritis is one of the most common life-threatening diseases in dogs. Immuno-suppression and intestinal barrier  disruption predispose affected dogs for sepsis and make them a suitable population to study sepsis. The present study focuses on the diagnostic  efficacy of faecal antigen test kit and on the occurrence of sepsis in canine parvovirus enteritis along with its association with morbidity and  mortality. Tentative diagnosis for CPV was based on clinical signs and haematology, confirmation was done by Snap® parvo antigen test kit  and PCR using faecal samples. Total 29 dogs between 6 weeks to 1 year of age were included comprising 6 healthy and 23 non-vaccinated  CPV positive dogs. Efficacy of diagnosing CPV via faecal antigen test kit was found to be 69.50%, while PCR showed 100% efficacy. The overall  occurrence of Systemic Inflammatory Response Syndrome (SIRS) on the day of presentation in CPV dogs was 60.80% and survivability with  SIRS was 71.43%. Blood culture revealed Staphylococcus spp. This study concludes that faecal antigen test kit gives rapid result with minimum  labour and cost, but might give false negative results, and identification of sepsis at early stage might help the clinician in shifting the patient  to more aggressive therapy.
Keywords: Antigen detection kit; Dogs; Parvovirus,; Sepsis; SIRS